Nursing care for the control of disabilities in elderly diabetics in primary health care (Research, Society and Development, 2020)
Objective: What are the nursing care for elderly diabetics to control disabilities in primary health care. Method: this is an Integrative Literature Review. The databases: LILACS, PUBMED and COCHRANE were used. Full articles were selected and available in English, Portuguese and Spanish. The results were analyzed using the IRAMUTEQ software, specifically the Reinert method and Descending hierarchical classification. Results: analyzed using IRAMUTEQ, there was a categorization into 5 classes: CLASS 1- The importance of management in optimizing the health-disease process in elderly people with diabetes mellitus in the setting of Primary Health Care; CLASS 2- The importance of using standard tools in directing nursing care decision-making; CLASS 3- Nursing care care to prevent complications of diabetes mellitus; CLASS 4- Health education as a strategy to raise awareness and improve the skills of the elderly; CLASS 5- The challenges encountered in orienting / assisting the elderly with diabetes mellitus. Conclusion: it is concluded that the nursing care most cited in the literature was health education, guidance on the health-disease process, vulnerability detection and actions to reduce structural damage.